Bioprocess engineering principles - Doran, Pauline M.
The emergence and refinement of techniques in molecular biology has changed our perceptions of medicine, agriculture, and environmental management. Scientific breakthroughs in gene expression, protein engineering, and cell fusion are being translated by a strengthening biotechnology industry into revolutionary new products and services. Many a student has been enticed by the promise of biotechnology and the excitement of being near the cutting edge of scientific advancement. However, graduates trained in molecular biology and cell manipulation soon realize that these techniques are only part of the picture. Reaping the full benefits of biotechnology requires manufacturing capability involving the large-scale processing of biological material. Increasingly, biotechnologists are being employed by companies to work in cooperation with chemical engineers to achieve pragmatic commercial goals. For many years, aspects of biochemistry and molecular genetics have been included in chemical engineering curricula, yet there has been little attempt until recently to teach aspects of engineering applicable to process design to biotechnologists.